Ethnopharmacological survey of Rwandese medicinal plants used for respiratory infections. Effect of Senecio maranguensis extract against respiratory syncytial virus - Colores Uwamariya; Jackson T. Mollel; Farshid M. Rad; Wouter A. Remmerswaal; Joanna Said; Charles Hannoun; Masum Miah; Ambjörn Kärmander; Daniel Umereweneza; Théoneste Muhizi; Eric Seruyange; Emile Bienvenu; et al. (Phytomedicine Plus, 2025)
Background: The knowledge of traditional health practitioners (THPs) on the use of medicinal plant remedies for treatment of human respiratory ailments provides a potential resource for identification of relevant plants and isolation of active ingredients. Purpose: We aimed to identify medicinal plants used by THPs for treatment of respiratory ailments, then screen them in cultured cells for activity against respiratory syncytial virus (RSV), and assess the antiviral potential of identified screening hits. Methods: Forty Rwandese THPs were interviewed to identify medicinal plants used for treatment of respiratory ailments. The indicated plant samples were collected and successively extracted using n-hexane, ethyl acetate, methanol, and water. Extracts were screened for anti-RSV activity and for cytotoxicity in HEp-2 cells. Results: Based on ethnopharmacological survey of THPs, 48 plants used for treating respiratory ailments were identified. Of 203 plant extracts prepared for screening, ten methanolic and four aqueous extracts exhibited anti-RSV activity, manifested by EC50 values ranging from 1.6 to 39.5 µg/ml and selectivity indices (SI, CC50/EC50) of 12–294. Extended studies of an anti-RSV potential of methanolic extract of Senecio maranguensis O. Hoffm. leaves revealed that this preparation targeted the virus fusion (F) protein because extract resistant virus variants carried the double nucleotide substitution at c1104t and a1105g resulting in the T335M amino acid change in the F protein trimer internal cavity. Conclusion: We found that eleven plants, traditionally used against respiratory ailments, exhibited substantial anti-RSV activity in cultured cells, exemplified by the S. maranguensis methanolic extract that affected the activity of RSV F protein.